The Resistance of Conservative Islamic Organizations on the Development of Regional Tourism in Madura - Abd Hannan (Tamaddun, 2021)
This study examines the resistance behavior of conservative Islamic organizations to regional tourism development in Madura, especially entertainment-based tourism. There are three research questions in this study: how is the reality of conservative Islamic organizations in Madura to the religious dynamics of the local community? How is the existence of conservative Islamic organizations to the dynamics of tourism development in Madura? How is the resistance of conservative Islamic organizations towards tourism development in Madura? Qualitative data were collected through observation, interview, and literatures study. The findings show: First, the conservativism values of Islamic organizations in Madura were born and spread widely from local traditions and religions; Second, the tradition of conservatism of Islamic organizations in Madura seen in several Islamic organizations, mainly right-wing Islamic organizations such as AUMA, FKM, and GUIP; Third, the conservatism of Islamic organizations in Madura is related to their resistant behavior towards tourism development in Madura, which reflect in their thinking and religious paradigms which tend to be traditionalist, puritanical, and reactionary. They use anarchism approaches that lead to violence, for instance burning the Bukit Bintang tourist site in Pamekasan Regency. Studi ini mengkaji perilaku resisten Ormas Islam konservatif terhadap pembangunan pariwisata daerah di Madura, khususnya pariwisata berbasis hiburan. Terdapat tiga pertanyaan penelitian pada studi ini: bagaimana realitas Ormas Islam konservatif di Madura dalam dinamika keagamaan masyarakat setempat? Bagaimana eksistensi Ormas Islam konservatif dalam dinamika pembangunan pariwisata di Madura? Bagaimana resistensi Ormas Islam konservatif terhadap pembangunan pariwisata di Madura? Kualitatif data dikumpulkan melalui observasi, wawancara, dan studi kepustakaan. Temuan studi ini menunjukan: Pertama, nilai-nilai konservatisme Ormas Islam di Madura lahir dan menyebar luas dari tradisi dan keagamaan lokal; Kedua, tradisi konservatisme Ormas Islam di Madura dapat ditemukan di sejumlah Ormas Islam, terutama Ormas Islam yang secara ideologi berhaluan kanan seperti AUMA, FKM, dan GUIP; Ketiga, konservatisme Ormas Islam di Madura terkait perilaku resisten mereka terhadap pembangunan pariwisata di Madura, tergambar pada paradigma berpikir dan keagamaan mereka yang cenderung tradisionalis, puritan, dan reaksioner. Mereka menggunakan pendekatan anarkisme sehingga berujung pada tindak kekerasan seperti pada kasus pembakaran lokasi wisata Bukit Bintang di Kabupaten Pamekasan.